Navigating the Curriculum Landscape: The Impact of Curriculum 2013 and Merdeka Curriculum on Teachers' and Students' Learning Outcomes in Indonesia - Rahmah, Laily; Purwanta, Edi; Wijayanti, Wiwik; Suhardiman, Sani (Journal of Ecohumanism, 2024)
This study explores the impact of implementing the 2013 Curriculum and the Independent Curriculum on teachers and student learning outcomes in Indonesia. The 2013 curriculum is designed to improve the competencies of 21st century students through a scientific approach and project-based learning. However, its implementation is limited, including the lack of teacher readiness and adequate infrastructure. On the other hand, the Independent Curriculum offers a more flexible and student-centered approach, focusing on character development and life skills. This study uses a mixed approach, involving surveys and in-depth interviews to analyze the perceptions of teachers and students from different regions. The study results show that the Independent Curriculum significantly increases student motivation and engagement, especially through a project-based learning approach. And more than 50% of teachers agree that the integration in independent curriculum is is more effective in helping teachers to design more effective in learning.. However, the main challenge in implementing this curriculum is the resource gap, especially in remote areas. Many teachers also have difficulty adjusting to more innovative teaching methods, although they welcome the flexibility offered by this curriculum. The study concludes that while the Independent Curriculum has the potential to improve the quality of learning, its success is highly dependent on the support of more intensive teacher training and the improvement of educational infrastructure. The main recommendation is the need for more focused efforts to ensure equal access to education and increase teacher capacity throughout Indonesia.